1974
DOI: 10.1042/bj1390565
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic acid in cartilage and proteoglycan aggregation

Abstract: 1. Dissociation of purified proteoglycan aggregates was shown to release an interacting component of buoyant density higher than that of the glycoprotein-link fraction of Hascall & Sajdera (1969). 2. This component, which produced an increase in hydrodynamic size of proteoglycans on gel chromatography, was isolated by ECTEOLA-cellulose ion-exchange chromatography and identified as hyaluronic acid. 3. The effect of pH of extraction showed that the proportion of proteoglycan aggregates isolated from cartilage wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
136
1
4

Year Published

1975
1975
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 344 publications
(149 citation statements)
references
References 38 publications
8
136
1
4
Order By: Relevance
“…G, CT, and E each degrade the larger of the two link proteins without affecting the smaller and without altering the immunological reactivity of the GPL fraction in which they are isolated. Although they serve to stabilize the proteoglycan aggregate under certain conditions in vitro (7,8,21), the link proteins are not necessary for aggregate formation (6). The link proteins appear to share antigenic determinants with PGS and it has been suggested that they may, in fact, be derived from PGS (21a); this suggestion is supported by the finding described here that prolonged digestion of PGS with E produces a link protein-like precipitin line (24).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…G, CT, and E each degrade the larger of the two link proteins without affecting the smaller and without altering the immunological reactivity of the GPL fraction in which they are isolated. Although they serve to stabilize the proteoglycan aggregate under certain conditions in vitro (7,8,21), the link proteins are not necessary for aggregate formation (6). The link proteins appear to share antigenic determinants with PGS and it has been suggested that they may, in fact, be derived from PGS (21a); this suggestion is supported by the finding described here that prolonged digestion of PGS with E produces a link protein-like precipitin line (24).…”
Section: Discussionsupporting
confidence: 75%
“…The main structural features of bovine nasal cartilage proteoglycan, as established by recent biochemical, physicochgmical, immunological, and electron-microscopic studies (2)(3)(4)(5)(6)(7)(8)(9)(10)(11), are illustrated in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…The two components observed by ultracentrifugation of such extracts were shown to be a proteoglycan subunit and glycoprotein link, which aggregated to form a protein-polysaccharide complex. Subsequently the aggregation has been shown to require the interaction of hyaluronate and a protein-rich fraction (Gregory, 1973;Hardingham & Muir, 1974;Hascall & Heinegard, 1974a,b;Heinegard & Hascall, 1974).…”
Section: (Received 9 September 1974)mentioning
confidence: 99%
“…It is present in very small quantities (< 1% of the total glycosaminoglycan composition) in connective tissue, where it plays an important role in the hierarchy of the tissue matrix. It is known to bind extensively to proteoglycan (Hardingham & Muir, 1974), thereby forming a hydrophilic aggregate that causes the inflation of the cartilage matrix. These extended aggregates are constrained within a network of collagen fibres.…”
Section: Study Of Hyaluronic Acid Flexibility By Electric Birefringencementioning
confidence: 99%